2009
DOI: 10.1172/jci37048
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial H2O2 emission and cellular redox state link excess fat intake to insulin resistance in both rodents and humans

Abstract: High dietary fat intake leads to insulin resistance in skeletal muscle, and this represents a major risk factor for type 2 diabetes and cardiovascular disease. Mitochondrial dysfunction and oxidative stress have been implicated in the disease process, but the underlying mechanisms are still unknown. Here we show that in skeletal muscle of both rodents and humans, a diet high in fat increases the H(2)O(2)-emitting potential of mitochondria, shifts the cellular redox environment to a more oxidized state, and dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

67
1,127
7
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,103 publications
(1,232 citation statements)
references
References 64 publications
67
1,127
7
8
Order By: Relevance
“…Overactivation of stress pathways such as oxidative and endoplasmic reticulum stress have been linked with insulin resistance [36][37][38], though there is also evidence that reactive oxygen species production and the unfolded protein response can positively influence insulin action [39,40]. Obese, insulin-resistant individuals also exhibit a state of chronic low-grade inflammation, and as such activation of inflammatory pathways have also been proposed as a major driver of insulin resistance [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Overactivation of stress pathways such as oxidative and endoplasmic reticulum stress have been linked with insulin resistance [36][37][38], though there is also evidence that reactive oxygen species production and the unfolded protein response can positively influence insulin action [39,40]. Obese, insulin-resistant individuals also exhibit a state of chronic low-grade inflammation, and as such activation of inflammatory pathways have also been proposed as a major driver of insulin resistance [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…In cultured cells there is experimental evidence that ROS have an inhibitory effect on insulin signalling [16,17]. Human studies have shown that obesity and high-fat diet increase mitochondrial hydrogen peroxide release [18]. Furthermore, a recent study showed that mitochondrial ROS release was higher in muscle of patients with type 2 diabetes than in obese controls, but similar to that observed in lean control participants [19].…”
Section: Introductionmentioning
confidence: 88%
“…H 2 O 2 production An aliquot of 0.1 mg isolated mitochondria was used to measure rates of H 2 O 2 production fluorimetrically by the Amplex Red method as described elsewhere [23]. Briefly, the emitted H 2 O 2 was selectively trapped by horseradish peroxidase, which uses Amplex Red as an electron donor during the reduction of H 2 O 2 to H 2 O.…”
Section: Methodsmentioning
confidence: 99%